Earth-Mars transfers through Moon Distant Retrograde Orbits. (February 2018) - Conte, Davide; Di Carlo, Marilena; Ho, Koki; Spencer, David B.; Vasile, Massimiliano
Abstract: This paper focuses on the trajectory design which is relevant for missions that would exploit the use of asteroid mining in stable cis-lunar orbits to facilitate deep space missions, specifically human Mars exploration. Assuming that a refueling "gas station" is present at a given lunar Distant Retrograde Orbit (DRO), ways of departing from the Earth to Mars via that DRO are analyzed. Thus, the analysis and results presented in this paper add a new cis-lunar departure orbit for Earth-Mars missions. Porkchop plots depicting the required C 3 at launch, v ∞ at arrival, Time of Flight (TOF), and total Δ V for various DRO departure and Mars arrival dates are created and compared with results obtained for low Δ V Low Earth Orbit (LEO) to Mars trajectories. The results show that propellant-optimal trajectories from LEO to Mars through a DRO have higher overall mission Δ V due to the additional stop at the DRO. However, they have lower Initial Mass in LEO (IMLEO) and thus lower gear ratio as well as lower TOF than direct LEO to Mars transfers. This results in a lower overall spacecraft dry mass that needs to be launched into space from Earth's surface. Highlights: Orbital transfers from Earth to Mars through lunar DROs are analyzed. Propellant-optimal solutions for Earth-lunar DRO-Mars transfers are presented. A basic architecture example of a lunar DRO "fuel depot" is shown. An overview of the role of a lunar DRO in space exploration is provided.